2004
DOI: 10.1007/s00424-003-1099-7
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial transporter family (SLC25): physiological and pathological implications

Abstract: The mitochondrial carriers (MCs) shuttle a variety of metabolites across the inner mitochondrial membrane (i.m.m.). In man they are encoded by the SLC25 genes. Some MCs have isoforms encoded by different SLC25 genes, whereas the phosphate carrier has two variants arising from an alternative splicing of SLC25A3. Six MCs have been sequenced after purification, and many more have been identified from their transport and kinetic properties following heterologous over-expression and reconstitution into liposomes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
580
0
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 691 publications
(595 citation statements)
references
References 62 publications
5
580
0
10
Order By: Relevance
“…This carrier transports only L-aspartate and L-glutamate, and its physiological role is to catalyze the exchange of intramitochondrial aspartate with cytosolic glutamate plus a proton (Palmieri 2004). To investigate whether the R353Q mutation of AGC1 affects protein function, we overexpressed the wild-type and mutant AGC1 proteins in Escherichia coli, purified the proteins, and reconstituted these purified proteins into phospholipid vesicles (liposomes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This carrier transports only L-aspartate and L-glutamate, and its physiological role is to catalyze the exchange of intramitochondrial aspartate with cytosolic glutamate plus a proton (Palmieri 2004). To investigate whether the R353Q mutation of AGC1 affects protein function, we overexpressed the wild-type and mutant AGC1 proteins in Escherichia coli, purified the proteins, and reconstituted these purified proteins into phospholipid vesicles (liposomes).…”
Section: Resultsmentioning
confidence: 99%
“…SLC25A12 encodes a neuronal-specific mitochondrial aspartate-glutamate carrier (aspartate-glutamate carrier isoform 1, AGC1). AGC1 is an important component of the neuronal malate/aspartate shuttle (Palmieri 2004), which is a crucial system to export intramitochondrial aspartate and to transfer the reducing equivalents of NADH from cytosol to mitochondria and hence to support oxidative phosphorylation (Lasorsa et al 2003). A distinct disorder, AGC2 deficiency, results from SLC25A13 mutations that reduce aspartate-glutamate carrier isoform 2 (AGC2) function with impaired malate/aspartate shuttle activity in the liver (Saheki and Kobayashi 2002).…”
Section: Discussionmentioning
confidence: 99%
“…25 Four AAC isoforms have been identified in human with distinct expression patterns. 26,27 According to previous reports, [28][29][30] AAC2 and AAC3 are the dominant AACs in ECs. Co-IP confirmed that ISM interacts with AAC2/AAC3 (Figure 5a).…”
Section: Resultsmentioning
confidence: 91%
“…Reconstitution into liposomes and complementation experiments in yeast revealed also common functional characteristics between the different MCs, although the substrates transported differ widely in their structure, charge and size [40].…”
Section: The Involvement Of Mitochondrial Carrier Proteins In Apoptosismentioning
confidence: 95%
“…The mitochondrial carrier (MC) protein family comprises of membrane embedded proteins that catalyze the exchange of solutes across the IMM (reviewed in [40,41]). These carriers provide a link between mitochondria and cytosol, which is indispensable for the metabolic activities performed by mitochondria.…”
Section: The Involvement Of Mitochondrial Carrier Proteins In Apoptosismentioning
confidence: 99%